Carbon nanotube-based nanocomposites and their applications - Ates, Murat; Eker, Aysegul Akdogan; Eker, Bulent (TAYLOR & FRANCIS LTD, 2017)
The purpose of the current review article is to present a compherensive understanding regarding pros and cons of carbon nanotube-related nanocomposites and to find ways in order to improve the performance of nanocomposites with new designs. Nanomaterials including carbon nanotubes (CNTs) are employed in industrial applications such as supercapacitors, and biosensors, and etc. The present article has been prepared in three main categories. In the first part, carbon nanotube types have been presented, as single-walled carbon nanotubes, multi-walled carbon nanotubes, and also equivalent circuit models, which have been used to more clarify the experimental measurements of impedance. In the second part, nanocomposites with many carbon, inorganic and polymeric materials such as polymer/CNT, activated carbon/CNT, metal oxide/CNT, and carbon fiber/CNT have been investigated in more detail. In the third part, the focus in on the industrial applications of CNTs. including supercapacitors, biosensors, radar absorbing materials, solar cells, and corrosion protection studies. This review article explains the latest advances in carbon nanotubes and their applications in electrochemical, electrical and optical properties of nanocomposites.
Keywords: Carbon nanotubes; nanocomposite; supercapacitor; multi-walled carbon nanotube; biosensor; radar absorbing materials; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY; MICROWAVE-ABSORBING PROPERTIES; HIGH-RATE PERFORMANCE; ACTIVATED CARBON; COMPOSITE ELECTRODES; FILM ELECTRODES; MECHANICAL-PROPERTIES; CORROSION PROTECTION; GRAPHENE NANOSHEETS; HYDROGEN EVOLUTION; Engineering; Materials Science; Mechanics